Cross-border bank flows, regional household credit booms and bank risk-taking - Dominik Boddin; Daniel Marcel te Kaat; Kasper Roszbach (Norges Bank, 2024)
This paper provides novel micro-level evidence that cross-border bank flows are important for households' access to credit not only in emerging markets but also in advanced economies. These foreign bank flows can drive local credit credit booms that increase bank risk. We study how the influx of cross-border bank funding that followed the ECB's implementation of non-conventional monetary policy in 2014/15 impacted lending to households, using supervisory bank-level data alongside householdlevel credit and consumption data from Germany. Regional banks that are highly exposed to fluctuations in foreign capital inflows increase consumer lending to riskier, lower-income households by 50% more than other banks. When deposit inflows from non-euro area banks rise, this induces less capitalized banks to expand their lending on the extensive margin. Improved access to credit enables lower-income customers of exposed banks to increase non-durable consumer spending. Data from a larger group of euro area countries confirm our conclusions.
hdl:11250/3172793
Keywords: F3; G2; G5; 330; Cross-Border Bank Flows; Households; Bank Lending; Risk-Taking; Credit Booms; Funding Shocks